Integrating Culturally Responsive Teaching and Differentiated Learning to Promote Critical Thinking in Chemistry Learning toward Sustainable Development Goal 4 - Fitriyuni Miralda Siregar; Yuli Rahmawati; Achmad Ridwan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To combine Culturally Responsive Teaching (CRT) and differentiated learning in chemistry instruction to increase student engagement and improve students’ critical thinking skills. Method: Qualitative research conducted at MA Pembangunan UIN Jakarta involving 32 students. The learning model was implemented in chemistry topics of hydrolysis and acid-base titration. Data were collected through interviews, observations, and reflective journals. Results: The implementation of CRT-integrated differentiated learning improved students’ critical thinking skills. Students were able to connect chemical concepts with relevant real-life experiences and cultural contexts. The approach also promoted active participation, collaboration, appreciation of cultural diversity, and an inclusive learning environment. Novelty: Proposing an integrated instructional framework that combines Culturally Responsive Teaching (CRT) and differentiated learning to foster students’ critical thinking in chemistry education while advancing Sustainable Development Goal (SDG) 4: Quality Education. The framework promotes inclusive, equitable, and culturally relevant learning by accommodating diverse student backgrounds and learning needs, thereby supporting both conceptual understanding and higher-order thinking skills.